Empowering and Supporting Remote Software Development Team Members through a Culture of Allyship - Rodeghero, Paige; Hernandez, Tony (2020)
ABSTRACT Software development organizations and employees benefit from remote work. However, we need more research and tools for more organizations to be successful. Microsoft is in a prime position to do the research, interventions and technology innovations need to advance the benefits of remote work. We discuss the benefits and challenges that remote workers face. We provide remote work guidelines based upon personal experiences of working remotely before the COVID-19 pandemic. In this position paper, we argue for employers to become allies for remote workers and to empower workers to work in their preferred environment. We provide ways to create a culture of allyship within organizations and teams. By creating a sustainable remote work environment and empowering remote employees, companies will find more productive employees with higher job satisfaction. Keywords remote work, inclusion, diversity, allyship ABOUT THE AUTHOR/S Paige Rodeghero Microsoft Research, Clemson University prodegh@clemson.edu Paige Rodeghero is a Visiting Researcher at Microsoft Research and an Assistant Professor of Computer Science at Clemson University. Her website is paigerodeghero.com Tony Hernandez Microsoft Tony.Hernandez@microsoft.com Tony Hernandez is a Software Engineer in the Customer Success Engineering organization within the Experience and Devices division at Microsoft. He also leads a virtual team focused on the remote onboarding of software engineers at Microsoft for the Content Publish engineering team. New Future of Work 2020, August 3–5, 2020 © 2020 Copyright held by the owner/author(s).